2013
DOI: 10.1002/jgrc.20135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Southern Ocean water mass circulation and characteristics in CMIP5 models: Historical bias and forcing response

Abstract: [1] The ability of the models contributing to the fifth Coupled Models Intercomparison Project (CMIP5) to represent the Southern Ocean hydrological properties and its overturning is investigated in a water mass framework. Models have a consistent warm and light bias spread over the entire water column. The greatest bias occurs in the ventilated layers, which are volumetrically dominated by mode and intermediate layers.The ventilated layers have been observed to have a strong fingerprint of climate change and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
234
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(265 citation statements)
references
References 60 publications
28
234
3
Order By: Relevance
“…Consequently, the flow of deep water masses in CNRM-ESM1 has been improved with regards to that of CNRM-CM5, which ranges between 3.4 and 6.2 Sv over the same period Voldoire et al, 2013). As detailed in several intercomparison studies (de Lavergne et al, 2014;Heuzé et al, 2013;Sallée et al, 2013;Séférian et al, 2013), CNRM-CM5 substantially underestimated the flow of AABW leading to an erroneous distribution of hydrodynamical and biogeochemical fields at depth. Here, although stronger than the observation-based estimates, the flow of NADW and AABW improves the deep ocean ventilation as well as the distribution of tracers at depth (Sect.…”
Section: Ocean Physical Driversmentioning
confidence: 99%
“…Consequently, the flow of deep water masses in CNRM-ESM1 has been improved with regards to that of CNRM-CM5, which ranges between 3.4 and 6.2 Sv over the same period Voldoire et al, 2013). As detailed in several intercomparison studies (de Lavergne et al, 2014;Heuzé et al, 2013;Sallée et al, 2013;Séférian et al, 2013), CNRM-CM5 substantially underestimated the flow of AABW leading to an erroneous distribution of hydrodynamical and biogeochemical fields at depth. Here, although stronger than the observation-based estimates, the flow of NADW and AABW improves the deep ocean ventilation as well as the distribution of tracers at depth (Sect.…”
Section: Ocean Physical Driversmentioning
confidence: 99%
“…The unique SO region benefits from the strong link between deep and surface ocean through the southern upwelling (Sallée et al, 2013a). Earlier studies analyzing the previous generation of ESMs also demonstrated that this region will be an important sink of future atmospheric CO 2 although the efficiency of the sink may decrease .…”
Section: Carbon Uptake Evolution In the Southern Oceanmentioning
confidence: 99%
“…Where the fronts flow around major topographic obstacles, hence developing large-scale meanders, departures from parallel flow conditions break the prevalent regime where cross-frontal transport is inhibited (Naveira Garabato et al 2011). Such ''hotspots'' of transport, or ''leaky jet'' segments, show enhanced effective eddy diffusivity, thus allowing more tracer transport across the fronts (Naveira Garabato et al 2011;Thompson and Sallée 2012;Sallée et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Error bars show the minimum and maximum of the observation-based datasets (on top of blue bars) and the CMIP5 multimodel standard deviation (on top of red bars) for each water mass class. The compilation of estimates from observations and the CMIP5 model ensemble, and the method used to find water mass boundaries, are described in Sallée et al (2013). A similar method was applied to the last 20 yr of CM2.6-miniBLING output.…”
mentioning
confidence: 99%